Circulating narratives: Theorizing narrative travel, translation and provocation - Fine, Michelle (PINS-Psychology in Society, 2017)
When I received the set of four essays from Hugo Canham1, I was deeply humbled by the trust and then swept by the responsibility of “translation”. A white woman in North America, trained as a social psychologist and critical participatory researcher, I was asked to reflect on a quartet of provocative articles created by talented writers from the Global South, who have carefully interpreted rich interviews voiced by South Africans narrating pain, poverty, violence and exclusion during apartheid and since, speaking through pride, desire and resistance. Across these textured layers of telling, listening and writing, the narratives sailed across oceans and over the equator, in search of yet another translation, to be offered up to audiences both near and far. With the modest transfer of texts, together we agree to delicately stitch a transnational project of resistance, re-vision, and responsibility – fraught and important.